EDUCATION ON THE IMPLEMENTATION OF ORGANIZATIONAL CITIZENSHIP BEHAVIORAL HEAD OF HAMLET IN THE MANAGEMENT OF SITULEUTIK TOURIST DESTINATION IN CIBEUREUM VILLAGE, BANJAR CITY - Lia Muliawaty; NR. Ruyani; Fitri Farizah; M. Yusuf (Ann Publisher, 2024)
The behavior is carried out without coercion or expecting any reward. The extraordinary quality of service and the dedication to work with high standards are clear signs that OCB's behavior is present in every village apparatus in the organization. This behavior describes the added value of employees, a form of prosocial behavior, namely positive, constructive, and meaningful social behavior that helps the village organization progress. The approach method used to achieve the output, the community involvement PKM program in the Organizational Citizenship Behavior (OCB) mechanism taught, will be adapted through socialization. These goals can be achieved through 2 (two) approaches. The PkM team accompanied the PkM participants to make a presentation related to the importance of OCB being understood to reach an understanding regarding the authority and implementation of programs carried out by Village Heads, Urban Villages, and related agencies, including the Banjar City Youth, Sports, and Tourism Office. This understanding is related to OCB because it can increase the effectiveness and welfare of the organization. This voluntary behavior creates a positive work environment, reduces conflict, and increases team collaboration. The discussion of OCB usually involves the application of this concept in the context of human resource management (HRM) and organizational strategy. Understanding and managing OCB can help organizations create a productive and positive work environment.